Hybrid Organizations : the Causes of Organizational Hybridization - Krzos, Grzegorz (Organizacje hybrydowe : identyfikacja przyczyn hybrydyzacji organizacji, 2010)
In this paper the reasons for hybrid approach in organizational structures projecting are described. There are some examples of hybrid structures in Polish enterprises and local governments. It seems that hybrid approaches are the examples of positive reaction of organizations towards the change in their inner reality and their environment. Dynamic evolution of hybrid structures in Polish companies is an example of a response that organizations and managers produce to the processes of change and renewal, occurring in the crucial moments of organizational life. This phenomenon occurs both in the growth phase and in the late phase of the organization. Observations show that traditional types of structures described in the literature are not the only ones in present organizations. At present, many organizations use hybrid structures.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 148, s. 205-214
Keywords: hybrid organizations; causes of organizational hybridization; hybrid structures